BEBAN DAN HARAPAN CAREGIVER DALAM MERAWAT ANGGOTA KELUARGA DENGAN GANGGUAN JIWA - Ni Made Sri Muryani (Bali Health Published Journal, 2019)
Background: Caregiver can discuss problems when treating patients, because there is a burden that must be borne by the caregiver both physically and emotionally. The burden that is happened during the treatment must be responded by a coping source both internally and externally. Coping resources can include family support, government support, and support from health workers. Objective of The Study: Explores in depth the meaning of caregiver's burdens and expectations in caring for family members with mental disorders. Methods: Design of qualitative research with interpretative phenomenology approach. Based on the inclusion criteria and the data saturation, then there are 9 participants who are willing to follow this research process. Data collection strategies used in depth interview techniques with semi-structured interview guidelines. Researcher conducted the data analysis using Intepretative Phenomenological Analysis (IPA). Result: It is found four themes in this study, there are: 1) Caregiver bears the burden, 2) Feels the home situation like a hospital, 3) Requires a support from family, government, and health personnel, and 4) Sincere and surrender to accept the situation. Conclusion: The results of this study indicate that caregivers bear various burdens ranging from physical burden to psychological burden and to overcome the burden, it requires support from family, government, and health workers.